An IEEE Xplore Database Literature Review Concerning Internet of Everything During 2020-2021 - Alqasemi, Fahd; Alhagree, Salah; Zahary, Ammar; Shaddad, Redhwan (Institute of Electrical and Electronics Engineers (IEEE), 2021)
For communication and computing sciences researchers, the Internet of Everything (IoE) is one of the most attractive topics. It is the field that represents the interconnection between the internet of things (IoT) and people's need for several kinds of technological services. Thus, some literature considers the modern ages as the IoE era. Smart city, 5G, and 6G become part of IoE vocabularies list, besides many techniques and applications that have been utilized by researchers for conducting IoE business and academic projects. In this study, IoE directions have been explored, so papers that have IoE in IEEE Xplores indexed terms have been investigated. Retrieved papers have been categorized and systematically reviewed. Diverse perspectives have been studied statistically, presented visually, and papers directions are reviewed carefully. The relations between categories have been counted and available information about the IoE world is introduced, the main goal was discovering IoE methods and applications, that have been presented from 2020 to 2021.